APLIKASI PUPUK ORGANIK KANDANG AYAM dan KONSENTRASI AIR KELAPA TERHADAP PERTUMBUHAN dan HASIL TANAMAN ERCIS (Pisum sativum L) - Riduan Sembiring; Sumatera Tarigan; Meriksa Sembiring (Universitas Quality, 2019)
The research was carried out in the Tigapanah Village Farmers' field, Tigapanah Subdistrict, Karo Regency, from March to June 2016, where altitude was ± 1200 meters above sea level, Adosol land. The aim of the study was to determine the chicken manure dosage and the concentration of coconut water and its interaction with the growth and yield of Ercis plants (Pisumsativum L). Factorial Randomized Group Design (RBD) 4 levels, factor I: dose acquisition 1) without manure (control) 2) chicken manure 2) 200 g / plant, 3) 300 g / plant, 4) 400 g / plant (A0 , A1, A2, and A3). Factor II. Concentration of coconut water 4 level 1) 0 ml / plant, 2) 100 ml / plant, 3) 200 ml / plant, 4) 300 ml / plant (K0, K1, K2, K3). The results of the study showed that the effect of using chicken manure was significantly different (p ˃ 0.05) on the growth of plant height, number of branches, pods and weights of Ercis plants except that the age began to flower. Giving a dose of coconut water also gave a significantly different effect (p ˃ 0.05) on the growth of plant height, number of branches, production of pods and production weights except age began to flower. The interaction of doses of chicken manure and doses of coconut water did not have a significant effect on all observed parameters.